UMP continues to operate Gambang Campus - UMP, PNC
Universiti Malaysia Pahang (UMP) can now confidently continue to operate its campus in Gambang after a significant real estate deal is sealed recently between its wholly owned subsidiary, UMP Holdings Sdn Bhd (UMPH), and landowners Frontier Bond (M) Sdn Bhd and MEC Industrial Park Sdn Bhd.